Hemodynamic Disturbances in the Early Phase After Subarachnoid Hemorrhage: Regional Cerebral Blood Flow Studied by Bedside Xenon-enhanced CT. Issue 1 (January 2018) - Engquist, Henrik; Lewén, Anders; Howells, Tim; Johnson, Ulf; Ronne-Engström, Elisabeth; Nilsson, Pelle; Enblad, Per; Rostami, Elham
Abstract : Background: The mechanisms leading to neurological deterioration and the devastating course of delayed cerebral ischemia (DCI) after subarachnoid hemorrhage (SAH) are still not well understood. Bedside xenon-enhanced computerized tomography (XeCT) enables measurements of regional cerebral blood flow (rCBF) during neurosurgical intensive care. In the present study, CBF characteristics in the early phase after severe SAH were explored and related to clinical characteristics and early clinical course outcome. Materials and Methods: Patients diagnosed with SAH and requiring mechanical ventilation were prospectively enrolled in the study. Bedside XeCT was performed within day 0 to 3. Results: Data from 64 patients were obtained. Median global CBF was 34.9 mL/100 g/min (interquartile range [IQR], 26.7 to 41.6). There was a difference in CBF related to age with higher global CBF in the younger patients (30 to 49 y). CBF was also related to the severity of SAH with lower CBF in Fisher grade 4 compared with grade 3. rCBF disturbances and hypoperfusion were common; in 43 of the 64 patients rCBF<20 mL/100 g/min was detected in more than 10% of the region-of-interest (ROI) area and in 17 patients such low-flow area exceeded 30%. rCBF was not related to the localization of the aneurysm; there was no difference in rCBF of ipsilateral compared with contralateral vascular territories. In patients who initially were in Hunt & Hess grade I to III, median global CBF day 0 to 3 was significantly lower for patients who were in poor neurological state at discharge compared with patients in good neurological state, 25.5 mL/100 g/min (IQR, 21.3 to 28.3) versus 37.8 mL/100 g/min (IQR, 30.5 to 47.6). Conclusions: CBF disturbances are common in the early phase after SAH. In many patients, CBF was heterogenic and substantial areas with low rCBF were detected. Age and CT Fisher grade were factors influencing global cortical CBF. Bedside XeCT may be a tool to identify patients at risk of deteriorating so they can receive intensified management, but this needs further exploration.